Coping Strategies in Competitive Swimming: The Role of Goal Attainment Expectancies - Galanis, Ευάγγελος; Hatzigeorgiadis, Αντώνης (Inquiries in Physical Education and Sport, 2020)
The purpose of the present study was to examine the relationship between goal attainment expectancies and approach/avoidance coping strategies during swimming competition. Participants were 62 swimmers (mean age 16.58 ± 2.74 years, mean competitive experience 6.96 ± 3.30 years). Before the competition, the swimmers indicated their goal time for the competition and assessed their expectation of achieving this goal on a 10-point scale. Immediately after the competition, they completed the Coping in Competition questionnaire (COC, Hatzigeorgiadis & Chroni, 2007), which includes six dimensions, three approach strategies (effort, planning and positive self-talk) and three avoidance strategies (cognitive disengagement, behavioral disengagement and denial). Based on the goal attainment expectancies, swimmers were divided into two groups (higher expectations, n= 33, and lower expectations, n= 29). Analysis of variance showed a significant effect on coping strategies: effort, F(1, 58) = 4.16, p<.05, planning, F(1, 58) = 6.92, p<.05, positive self-talk, F(1, 58) = 4.92, p<.05, and behavioral disengagement, F(1, 58) = 3.83, p=.05. The mean scores showed that the higher goal attainment expectancies group had higher scores on the effort, planning, positive self-talk, and lower scores on the behavioral disengagement compared to the lower goal attainment expectancies group. Overall, the results suggest that the pursuit of appropriate goals, but also the cultivation of self-confidence in relation to these goals affect the cognitive and behavioral reactions of swimmers in the competition.